Post-tonsillectomy pain control with pre-incisional infiltration of bupivacaine - Mahmood, Mohammed Othman; Abdulla, Dler A.; Shahabaddin, Lana Abdulrazzak (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: Tonsillectomy is one of the most common surgeries, and post-operative pain is one of the most common inevitable sequel. Although various post-operative analgesia are used, pain is still an issue needed to be handled more thoroughly to gain early oral intake, less hospital stay, and early return to normal life. Thus, efforts are made to employ pre-emptive analgesia and achieve more relief. This study evaluated the effectiveness of pre-incisional peri-tonsillar (subcapsular) infiltration of bupivacaine in decreasing the post-tonsillectomy pain. Methods: The study design is a prospective single-blinded controlled intra-individual study wielding a convenience sample of 45 patients of both genders, aged 14-40 years underwent tonsillectomy. Under general anesthesia, left tonsillar fossa infiltrated with 3cc of bupivacaine 0.5, leaving the other side free as a control side. After a wait time of 10 minutes while operating right side, left tonsillectomy done. post-operative pain was assessed using a visual analogue scale (VAS) on ½, 2, 4 and 6 hours pos-operatively. Results: The mean age of the study participants was 24.44±6.959, and they included 29 (64.4) females and 16 (35.6) males. Seven patients (15.6%) showed no pain difference between left (test) side and right (control) side while 38 patients (84.4%) had a significant difference. The test side mean pain score was 1.01±0.64, and the control side mean pain score was 2.24±1.18 (P <0.001). Conclusion: Infiltration of 3cc bupivacaine with a latent period of 10 minutes reduces the post-tonsillectomy pain by around two folds without any additional analgesia in the initial six hours.